Nonlinear relationship between estimated pulse wave velocity and chronic kidney disease: analyses of NHANES 1999–2020 - Li, Wenshi; Xu, Rui; Yan, Honghao; Li, Zhan; Sun, Jiale; Wang, Lin (Frontiers in Medicine, 2025)
BackgroundLimited data on the correlation between estimated pulse wave velocity (ePWV) and chronic kidney disease (CKD) necessitate further investigation. This study aims to explore the association between ePWV and the prevalence of CKD.MethodsA cross-sectional study was conducted with 41,411 participants from the 1999–2020 National Health and Nutrition Examination Survey (NHANES). ePWV was calculated using an established equation from the Reference Values for Arterial Stiffness Collaboration, incorporating age and mean blood pressure. CKD prevalence was assessed as the primary outcome. Weighted logistic regression and linear models were applied for statistical analysis, with Restricted Cubic Splines (RCS) used to evaluate potential nonlinear associations. Subgroup analyses were conducted to assess variations and ensure the robustness of results.ResultsHigher ePWV was consistently associated with an increased prevalence of CKD. RCS analysis identified a significant positive nonlinear relationship. Subgroup analyses revealed sex-based and glucose metabolism abnormality-based differences, highlighting interactive correlations that provided further insights into the ePWV-CKD relationship.ConclusionThis study demonstrates a strong positive association between ePWV and CKD prevalence, underscoring the importance of monitoring arterial stiffness. The use of RCS and subgroup analyses enriched the findings and offered valuable directions for future research.